Analisis Keterampilan Memecahkan Masalah Melalui Model Problem Based Learning (PBL) Berbantuan Liveworksheets Pada Materi Gelombang Mekanik (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2025)
Mastering problem-solving is one of the crucial skills for thriving in the 21st century. This study investigates the profile of problem-solving skills on mechanical wave content after learning through Problem-Based Learning (PBL) assisted by liveworksheets. The research was designed using the R&D method with the 4D model encompassing the Define to Disseminate stages. The limited trial involved 70 twelfth-grade students, while the field test included 33 eleventh-grade students. The participants were selected using a cluster random sampling technique. The analysis included assessments of instrument validity and reliability, the effect on problem-solving skills, and the profile of students’ skills. The results showed that the problem-solving skills instrument used had validity and reliability in the high enough category. The results showed that the problem-solving skills instrument used had validity and reliability in the high enough category. The overall scores for the problem-solving skill indicators increased, ranging from poor to excellent category. The scores for each indicator were as follows: 89,39 for problem comprehension; 75,38 for designing the problem-solving procedure; 85,61 for executing the procedure; and 85,23 for evaluating the overall problem-solving process. These results suggest that the use of the PBL assisted by liveworksheets has a positive impact on problem-solving. Consequently, this study emphasizes the potential of integrating the PBL model with digital technology as an alternative instructional approach to enhance problem-solving.